Chronic Ethanol Metabolism Inhibits Hepatic Mitochondrial Superoxide Dismutase via Lysine Acetylation. (14th September 2017) - Assiri, Mohammed A.; Roy, Samantha R.; Harris, Peter S.; Ali, Hadi; Liang, Yongliang; Shearn, Colin T.; Orlicky, David J.; Roede, James R.; Hirschey, Matthew D.; Backos, Donald S.; Fritz, Kristofer S.
Abstract : Background: Chronic ethanol (EtOH) consumption is a major cause of liver disease worldwide. Oxidative stress is a known consequence of EtOH metabolism and is thought to contribute significantly to alcoholic liver disease (ALD). Therefore, elucidating pathways leading to sustained oxidative stress and downstream redox imbalances may reveal how EtOH consumption leads to ALD. Recent studies suggest that EtOH metabolism impacts mitochondrial antioxidant processes through a number of proteomic alterations, including hyperacetylation of key antioxidant proteins. Methods: To elucidate mechanisms of EtOH‐induced hepatic oxidative stress, we investigate a role for protein hyperacetylation in modulating mitochondrial superoxide dismutase (SOD2) structure and function in a 6‐week Lieber–DeCarli murine model of EtOH consumption. Our experimental approach includes immunoblotting immunohistochemistry (IHC), activity assays, mass spectrometry, and in silico modeling. Results: We found that EtOH metabolism significantly increased the acetylation of SOD2 at 2 functionally relevant lysine sites, K68 and K122, resulting in a 40% decrease in enzyme activity while overall SOD2 abundance was unchanged. In vitro studies also reveal which lysine residues are more susceptible to acetylation. IHC analysis demonstrates that SOD2 hyperacetylation occurs near zone 3 within the liver, which is the main EtOH‐metabolizing region of the liver. Conclusions: Overall, the findings presented in this study support a role for EtOH‐induced lysine acetylation as an adverse posttranslational modification within the mitochondria that directly impacts SOD2 charge state and activity. Last, the data presented here indicate that protein hyperacetylation may be a major factor contributing to an imbalance in hepatic redox homeostasis due to chronic EtOH metabolism. Abstract : Oxidative stress is a known consequence of ethanol (EtOH) metabolism and is thought to contribute significantly to the pathogenesis of alcoholic liver disease (ALD). Chronic EtOH consumption induces lysine acetylation of many metabolic and antioxidant proteins. Here, we demonstrate that EtOH metabolism hyperacetylates mitochondrial superoxide dismutase (SOD2) and contributes to the inhibition of SOD2 activity. These results suggest that mitochondrial protein hyperacetylation may be a major factor contributing to an imbalance in hepatic redox homeostasis due to chronic EtOH metabolism.